2014
DOI: 10.1080/0966369x.2014.885888
|View full text |Cite
|
Sign up to set email alerts
|

Local gender contract and adaptive capacity in smallholder irrigation farming: a case study from the Kenyan drylands

Abstract: This paper presents the local gender contract of Sibou, Kenya: a smallholder irrigation farming community.Women's role in subsistence farming in Africa has mostly been analyzed through the lens of gender division of labor. In addition to this, we used the concept of 'local gender contract' to analyze cultural and material preconditions shaping gender-specific tasks in agricultural production, and consequently, men's and women's different strategies for adapting to climate variability. We show that the introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 29 publications
(26 reference statements)
0
27
0
Order By: Relevance
“…Water control is an expression of masculinity which hinders women´s access to resources, especially if they are widows or their husbands is absent. Often they might find themselves in the situation where they have to pay a man to be able to keep their crops from dry up and dying putting in jeopardy the wellbeing of their children (Caretta and Börjeson, 2015). Through these activities, Harambees are truly a life saver for women.…”
Section: Women's Harambee In East Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Water control is an expression of masculinity which hinders women´s access to resources, especially if they are widows or their husbands is absent. Often they might find themselves in the situation where they have to pay a man to be able to keep their crops from dry up and dying putting in jeopardy the wellbeing of their children (Caretta and Börjeson, 2015). Through these activities, Harambees are truly a life saver for women.…”
Section: Women's Harambee In East Africamentioning
confidence: 99%
“…Her research explicitly focuses on how women´s microcredit groups actively adapt to climate variability (Caretta and Börjeson, 2015), while carrying out her current research in Kenya and Tanzania, she observed women groups engaging in shared activities: saving, self-help, mutual support in agriculture, traditional dance and beading of decorations. Traditional networks of mutual support have long been present in Sub Saharan Africa.…”
Section: Women's Harambee In East Africamentioning
confidence: 99%
“…Group dynamics created gendered systems of belongings which appear to be important to maintaining LGC structures. The group and community dimensions were briefly mentioned by Hirdman (1990) and tentatively studied by Caretta and Börjeson (2015), but never operationalized in the analysis of gender contract.…”
Section: Maneuverabilitymentioning
confidence: 99%
“…In more recent developments, gender contracts have been studied at the individual level for instance research regional variations of gender contract in Sweden (Forsberg, 2010) and local gender contracts in Norway (Grimsrud, 2011;Gerrard, 2011); housing conflicts in Southern Africa (Larsson and Schlyter, 1995); women´s self-help housing in Botswana (Kalabamu, 2005); the renegotiation of the LGC in Laos due to the rubber boom (Lindeborg, 2012), gender adaptive capacity to climate change in Kenya (Caretta and Börjeson, 2015) and landscape formation in East Africa (Caretta, 2015b).…”
Section: Local Gender Contractmentioning
confidence: 99%
See 1 more Smart Citation